Just health meeting health needs fairly - Daniels, Norman 1942- (Cambridge University Press, 2012)
In this book by the award-winning author of Just Healthcare, Norman Daniels develops a comprehensive theory of justice for health that answers three key questions: what is the special moral importance of health? When are health inequalities unjust? How can we meet health needs fairly when we cannot meet them all? Daniels' theory has implications for national and global health policy: can we meet health needs fairly in ageing societies? Or protect health in the workplace while respecting individual liberty? Or meet professional obligations and obligations of justice without conflict? When is an effort to reduce health disparities, or to set priorities in realising a human right to health, fair? What do richer, healthier societies owe poorer, sicker societies? Just Health: Meeting Health Needs Fairly explores the many ways that social justice is good for the health of populations in developed and developing countries
Keywords: Ethik; Medical policy / Moral and ethical aspects; Health services accessibility; Right to health; Equality / Health aspects; Justice (Philosophy); Medical ethics; Medizinische Versorgung; Sozialethik; Soziale Gerechtigkeit; Gesundheitsfürsorge